2010
DOI: 10.1111/j.1365-2621.2010.02385.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioaccessibility of β‐carotene from yellow‐orange vegetables and green leafy vegetables by domestic heat processing

Abstract: Effect of heat treatment involved in domestic cooking on the bioaccessibility of b-carotene from yelloworange as well as green leafy vegetables was evaluated. Heat treatment of these vegetables by pressurecooking, stir-frying and open-pan boiling had a beneficial influence on the bioaccessibility of b-carotene. The extent of increase in the per cent bioaccessibility of b-carotene as a result of pressure-cooking was 21-84%. Stir-frying in presence of a small quantity of oil brought about an enormous increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
1
25
0
2
Order By: Relevance
“…A modified method described by Veda, Platel, and Srinivasan () was employed for extraction and subsequent determination of bioaccessible total carotenoid from aqueous fractions of samples. A suitable volume of aqueous fractions was added to acetone (1:1; v/v) followed by petroleum ether (2:1; v/v) and mixed for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified method described by Veda, Platel, and Srinivasan () was employed for extraction and subsequent determination of bioaccessible total carotenoid from aqueous fractions of samples. A suitable volume of aqueous fractions was added to acetone (1:1; v/v) followed by petroleum ether (2:1; v/v) and mixed for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Petroleum ether layer collection and recording of the OD of extraction was performed as it is described for raw and cooked samples. Percent bioaccessibility (%) was calculated as the percentage of carotenoid estimated in aqueous fraction (µg/100 g) to the carotenoid content in the cooked sample (µg/100 g) as described by Veda, Platel, and Srinivasan ().…”
Section: Methodsmentioning
confidence: 99%
“…Lipkie et al (2013) also observed improved bioaccessibility with addition of 10% oil in porridge prior to simulated digestion. Stir-frying of carotene-rich food was reported to lead to high carotene bioaccessibility (Garrett et al, 2000;Veda et al, 2010). Authors attributed improved carotene micellarisation efficiency to addition of oil, as oil can facilitate incorporation of carotene into the mixed micelle during digestion.…”
Section: In Vitro B-carotene Bioaccessibility In Ofsp Productsmentioning
confidence: 99%
“…Green leafy vegetables, red palm oil (RPO) and palm nuts are grown and consumed throughout West Africa. Depending on soil and agro-climatic conditions, these foods can be rich in b-carotene (Shukla & Singh, 2000;Veda et al, 2010). In Africa and Asia, amaranth leaves (Amaranthus cruentus) are an inexpensive source of protein, carotenoids, vitamin C, dietary fibre and essential minerals (Prakash & Pal, 1991;Shukla et al, 2003Shukla et al, , 2006Adebooye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…blanching, boiling, cooking, frying) have very distinct effects on the carotenoid pattern of processed food (Mayer-Miebach & Spiesz, 2003). While the heat treatment involved in cooking is a necessary step in making the food palatable and in improving the digestibility of food components, undesirable changes associated with cooking are a reduction in micronutrient contents caused by chemical reactions (Veda et al, 2010). At lower temperatures (60 -100°C), most carotenoids are well retained and isomerisation is negligible during blanching, pasteurisation, cooking, low temperature drying and frying (Maiani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%